AUDIT PROCEDURE FOR ACCOUNTS RECEIVABLE ON PT.SAHABAT MIO BY PUBLIC ACCOUNTING FIRMS - Minggu (ASIAN PUBLISHER, 2023)
The purpose of this study is to find out how the accounts receivable audit procedure is applied by the Public Accounting Firm, the focus of the discussion includes assessing the evaluation of internal control, making a top schedule and supporting schedule to sending confirmation of receivables. The research methodology used is in the form of field studies by observation and literature studies by studying various forms of written material, as well as interviews with companies. Based on the observations made by the author, it can be concluded that in general the audit procedure on accounts receivable has been implemented properly, it's just that the existing functions are still not in accordance with the existing ones